2014
DOI: 10.1155/2014/434960
|View full text |Cite
|
Sign up to set email alerts
|

On the Differences in the Intraseasonal Rainfall Variability between Western and Eastern Central Africa: Case of 10–25-Day Oscillations

Abstract: In this paper, we analyze the space-time structures of the 10–25 day intraseasonal variability of rainfall over Central Africa (CA) using 1DD GPCP rainfall product for the period 1996–2009, with an emphasis on the comparison between the western Central Africa (WCA) and the eastern Central Africa (ECA) with different climate features. The results of Empirical Orthogonal Functions (EOFs) analysis have shown that the amount of variance explained by the leading EOFs is greater in ECA than WCA (40.6% and 48.1%, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Those identified using the GPCP dataset were generally in similar locations as those shown in Figure 1 (not shown). The 29°E longitude was chosen to divide Equatorial Africa (defined above) into WEA and EEA for consistency with previous studies (e.g., see Sandjon et al ., 2014, Figure 1) and with an operational weather forecasting model over Lake Victoria in EEA (e.g., see Woodhams et al ., 2018, Figure 1). The sub‐regions over ocean and those whose base‐points were located on 29°E were disregarded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those identified using the GPCP dataset were generally in similar locations as those shown in Figure 1 (not shown). The 29°E longitude was chosen to divide Equatorial Africa (defined above) into WEA and EEA for consistency with previous studies (e.g., see Sandjon et al ., 2014, Figure 1) and with an operational weather forecasting model over Lake Victoria in EEA (e.g., see Woodhams et al ., 2018, Figure 1). The sub‐regions over ocean and those whose base‐points were located on 29°E were disregarded.…”
Section: Resultsmentioning
confidence: 99%
“…A few areas in central Equatorial Africa experience a bimodal rainfall cycle, while those outside the 5°S–5°N latitudinal band experience a unimodal rainfall cycle (e.g., Dunning et al ., 2016). Precipitation in Equatorial Africa is characterized by remarkable spatial variation at intraseasonal (e.g., Nguyen and Duvel, 2008), seasonal (e.g., Sandjon et al ., 2014; Fotso‐Kamga et al ., 2019) and interannual (e.g., Janowiak, 1988, Figure 2e) timescales. Because of the heterogeneity of precipitation over this region, previous studies delineated their areas of study into smaller sub‐regions, using either monthly totals (e.g., Indeje et al ., 2000; Dezfuli, 2011) or annual totals (e.g., Badr et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that in the tropics, the MJO is the dominant phenomenon of the atmospheric variability at intraseasonal timescales (10-90 days) (Madden and Julian 1994;Tazalika and Jury 2008;Tchakoutio et al 2014). In addition, many authors showed that MJO is largely responsible for the intraseasonal climate variance in the tropics and subtropics (Singh et al 1992;Mapande and Reason 2005;Pohl and Camberlin 2007;Maloney and Jeffrey 2008;Farnaz et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The notion of intraseasonal timescale then raised in the scientific community and since then, many authors studied the characteristics of intraseasonal rainfall variability in some regions in the tropics (e.g. Madden & Julian, 1971;Madden & Julian, 1972;Anderson et al, 1984;Madden & Julian, 1994;Sultan & Janicot, 2001;Jury & Mpeta, 2001;Tazalika & Jury, 2008;Maloney & Jeffrey, 2008;Tchakoutio et al, 2012;Tchakoutio et al, 2013a;Tchakoutio et al, 2013b;Tchakoutio et al, 2014). But the documentation on intraseasonal variability in tropical Africa is highly based on West Africa, East Africa and Southern Africa (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This confirms that CA a serious gap in the study of the tropical climate variability, though it is well-known that the intraseasonal modes such as MJO can substantially modulate rainfall variability at various timescales. In recent years, some authors started addressing the problem (Tchakoutio et al, 2012(Tchakoutio et al, , 2013a(Tchakoutio et al, , 2013b(Tchakoutio et al, , 2014, but in spite of their findings, the key challenge remains the best parameterization of ISOs for their use in the improvement of the rainfall prediction in tropical Africa.…”
Section: Introductionmentioning
confidence: 99%